Compressible AgNWs/Ti3C2Tx MXene aerogel-based highly sensitive piezoresistive pressure sensor as versatile electronic skins. Issue 38 (24th September 2020) - Bi, Lili; Yang, Zhonglin; Chen, Liangjun; Wu, Zhen; Ye, Cui
Abstract : AgNWs/Ti3 C2 T x MXene aerogel with well-aligned layer structure was prepared by a directional freezing strategy, and applied to fabricate piezoresistive pressure sensor, which has ultrahigh sensitivity (645.69 kPa −1 ) and low detection limit (1.25 Pa). Abstract : Wearable pressure sensors have been intensively studied as electronic skins, stimulated by the demand for a piezoresistive sensing system that is highly sensitive over an ultrawide pressure range. Herein, a wearable and flexible piezoresistive pressure sensor is developed by assembling a new type of composite aerogel in a sandwich structure. Directional freezing is applied to prepare the silver nanowires (AgNWs)/Ti3 C2 T x MXene-based compressible composite aerogel, in which 2D Ti3 C2 T x, with plentiful functional terminals acting as building skeletons, can reinforce the AgNWs aerogel and the interweaving of 1D AgNWs among Ti3 C2 T x layers averts stacking. In terms of the synergistic effect, the acquired composite aerogel is endowed with a well-aligned layer structure. The as-prepared piezoresistive pressure sensor exhibits ultrahigh sensitivity (645.69 kPa −1 ) with a detection limit of 1.25 Pa in a wide detection range (0–9 kPa), a short response time (60 ms), and superior bendable performance with a bending angle from 30° to 90°. Additionally, after undergoing more than 1000 compression cycles, it maintains a stable piezoresistive response. The well-aligned AgNWs/Ti3 C2 T x aerogel reveals its application potential in the wearable healthcare field.